Salivary pH and buffering capacity in early and late human immunodeficiency virus infection - Mithra N Hegde; Amit Malhotra; Nidarsh D Hegde (Wolters Kluwer Medknow Publications, 2013)
Background: Human immunodeficiency virus (HIV) causes severe immunosuppression due to progressive decrease in the CD4 T lymphocyte cells during the course of the disease and this affects all the body systems including glandular secretions. A number of lesions affecting the salivary glands have been noted in HIV infection. The objective of this study was to evaluate the salivary pH and the buffering capacity in HIV positive individuals and comparing it with the HIV negative healthy individuals. Materials and Methods: The study was carried out on 200 HIV positive subjects aged 20-40 years, divided into two groups on the basis of CD4 count and 100 HIV negative healthy individuals as control group. Both unstimulated and stimulated saliva were collected and the pH and buffering capacity ascertained using the saliva check kit. (GC Asia Dental Pvt. Ltd., Singapore, 508724). Results: All the three groups were compared using the ANOVA and it was found there was highly significant decrease in pH and buffering capacity with increase in immunosuppression. The intergroup comparison was carried out using the Tukey honestly significant difference (HSD) and the Chi square test. Group 1; CD4 count <200 and Group 2, CD4 count >200 showed a significant decrease in unstimulated salivary flow, stimulated salivary flow, and pH in comparison to HIV negative individuals; however, change in buffering capacity in Group 2 was not significant. Conclusion: There is a decrease in pH and buffering capacity in HIV infected patients. This decrease may be one of the factors responsible for increased caries in HIV infected population.